ИННОВАЦИОННАЯ ДЕЯТЕЛЬНОСТЬ – СТАНОВЛЕНИЕ, РАЗВИТИЕ, СТРУКТУРА - Аймухаммедова, Т.К. (SCIENCE and SOCIETY, 2016)
The article presents data on the origin of the word "innovation", the causes of innovation, formation, development, and the role of innovation in the development of human progress. The work contains detailed information about the origin of the science of the study of innovation - Innovation and the role of pedagogical innovations in the reform of the education system.